LACK OF STUDENTS' VOCABULARY REPERTOIRE IN LEARNING ENGLISH - Valentine, Ravina (English Language Teaching Prima Journal (ELT), 2025)
This classroom action research investigated the use of instructional media to improve students’ vocabulary repertoire in English learning at Markus Middle School in Medan. The study involved 26 ninth-grade students and was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Instructional media such as English songs, visual aids, and vocabulary games were integrated into the teaching process to enhance student engagement and vocabulary acquisition. Data were collected through vocabulary tests, classroom observations, and student questionnaires. The findings revealed a significant improvement in students’ vocabulary performance, with mean scores increasing from 30.76% in the diagnostic test to 60.76% by the end of Cycle II. Moreover, student engagement and motivation increased notably when instructional media were used. The study concludes that instructional media can be an effective strategy to support vocabulary development in EFL classrooms. It also emphasizes the importance of combining engaging content with scaffolding techniques to ensure comprehension and learner success.